2019
DOI: 10.1037/str0000098
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotional regulation ability, personality, and burnout among Spanish teachers.

Abstract: We aimed to gain a better understanding of the personality-burnout process by examining the effects of emotional regulation ability through both cross-sectional and a pre-post social and emotional learning intervention studies. The sample was composed of 243 Spanish public school teachers. Data were collected using the Maslach Burnout Inventory-Educators Survey, the Big Five Inventory, and the Mayer-Salovey-Caruso Emotional Intelligence Test. Our results indicated that emotional regulation ability significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 50 publications
(83 reference statements)
2
44
0
5
Order By: Relevance
“…For township public health workers, the role of interpersonal relationships at work is more important than for county and city workers due to the rural culture in China. Thus, the burnout problem of township public health workers must be addressed by developing intervention programmes focusing on interpersonal and emotional abilities, such as communication, stress adjustment and emotional control (Castillo‐Gualda, Herrero, Rodriguez‐Carvajal, Brackett, & Fernandez‐Berrocal, ).…”
Section: Discussionmentioning
confidence: 99%
“…For township public health workers, the role of interpersonal relationships at work is more important than for county and city workers due to the rural culture in China. Thus, the burnout problem of township public health workers must be addressed by developing intervention programmes focusing on interpersonal and emotional abilities, such as communication, stress adjustment and emotional control (Castillo‐Gualda, Herrero, Rodriguez‐Carvajal, Brackett, & Fernandez‐Berrocal, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, extraversion is associated with the use of rational strategies to solve problems and to seek social support [14]. Therefore, it is not surprising that empirical studies have shown an inverse relationship between extraversion and professional burnout [25,26].…”
Section: Influence Of the Individual Factors On Hardinessmentioning
confidence: 99%
“…Research has confirmed that suffering burnout has important consequences for the mental (frustration, dissatisfaction, guilt, anxiety, or depression) and physical health (psycho-somatic problems, cardiovascular diseases, or musculoskeletal disorders) of individuals [29,30]. Concretely, in the school environment burnout is a high risk factor.…”
Section: Introductionmentioning
confidence: 99%
“…They are able to recognize the value of emotions as a function of the situation and commit to them, or move away from them, depending on their usefulness. Further, they have the ability to discern which strategy is most appropriate when dealing with a specific emotion [29].…”
Section: Introductionmentioning
confidence: 99%